Penguatan Budaya Tenun ATBM Lurik Khas Pedan Klaten - Moh. Rusnoto Susanto; Rahayu Retnaningsih; Flora Grace Putrianti; Shafa’ Selimanorita; Puspa Eka Ayu Febriana (Abdi Seni, 2022)
It is very rare to find an integrated textile industry center in Indonesia until now, apart from the integrated textile industry with Pekalongan batik in Central Java which is synergistic with the growth of the fashion business and the proliferation of tailor and fashion design. However, this landscape can be found in Pedan Klaten District, which is a center for ATBM weaving production whose business growth is getting stronger into an integrated area. The original ATBM weaving of Pedan Klaten has been known to be very skilled and detailed in its workmanship so that the resulting product is very smooth and compact, with the main motif called lurik. The participatory approach of the colleague team and partners of the Lurik Pedan ATBM Weaving MSMEs with various strengthening programs includes: design training, technical development workshops, IPR regulations and other E-Commerce strengthening activities. This article is intended to explain field findings with a clear, objective, systematic, and careful description of the facts obtained. The results of the MSME assistance program for 1 year made impacts as follows; (1) The Lurik Pedan brand encourages the pioneering of an integrated cultural tourism industry area. (2) Strengthening the Marketing Communication (MARCOM) system as an effort to increase sales turnover and strengthen business strategy. (3) The strategy of strengthening the ATBM weaving culture for traditional Lurik weaving craftsmen in Pedan Klaten